2015
DOI: 10.1016/j.virol.2014.11.016
|View full text |Cite
|
Sign up to set email alerts
|

The tight junction protein JAM-A functions as coreceptor for rotavirus entry into MA104 cells

Abstract: Several molecules have been identified as receptors or coreceptors for rotavirus infection, including glycans, integrins, and hsc70. In this work we report that the tight junction proteins JAM-A, occludin, and ZO-1 play an important role during rotavirus entry into MA104 cells. JAM-A was found to function as coreceptor for rotavirus strains RRV, Wa, and UK, but not for rotavirus YM. Reassortant viruses derived from rotaviruses RRV and YM showed that the virus spike protein VP4 determines the use of JAM-A as co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
44
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(46 citation statements)
references
References 38 publications
(45 reference statements)
2
44
0
Order By: Relevance
“…Thus, it is suggested that there is a correlation between the injury of epithelial barrier and damage to tight junction complexes. The tight junction of epithelial cells is a multi-functional complex consisting of many proteins (29,30), including occludin, claudins and actin. As a large protein family, there are a number of claudin subtypes with diverse functions (31,32).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it is suggested that there is a correlation between the injury of epithelial barrier and damage to tight junction complexes. The tight junction of epithelial cells is a multi-functional complex consisting of many proteins (29,30), including occludin, claudins and actin. As a large protein family, there are a number of claudin subtypes with diverse functions (31,32).…”
Section: Discussionmentioning
confidence: 99%
“…Other proposed receptors for rotavirus cell entry include integrins 210 , heat shock protein 70 (REFS 211,212) and junctional proteins such as junctional adhesion molecule A, occludin and tight junction protein ZO-1 (REF. 213). After initial binding, VP7 and the VP5* domain of VP4 can interact with several of these co-receptors, which are concentrated at lipid rafts to mediate viral entry.…”
Section: Figurementioning
confidence: 99%
“…Second, TJ components can have a direct role in viral entrance. For example, CLDN1 is used as a co-receptor during viral infection to mediate entry in the liver [124][125][126]. During rotavirus infection, JAM-A was shown to function as a co-receptor for virus entrance in epithelial kidney cells [126].…”
Section: Therapeutic Approaches and Caveatsmentioning
confidence: 99%
“…For example, CLDN1 is used as a co-receptor during viral infection to mediate entry in the liver [124][125][126]. During rotavirus infection, JAM-A was shown to function as a co-receptor for virus entrance in epithelial kidney cells [126]. This points toward a possible, yet unstudied, therapeutic approach in which TJ proteins could be targeted to prevent viral entry at the BCSFB during viral infection in the brain (e.g., viral meningitis).…”
Section: Therapeutic Approaches and Caveatsmentioning
confidence: 99%